2022
DOI: 10.3390/ijms23169432
|View full text |Cite
|
Sign up to set email alerts
|

IgA Antiphospholipid Antibodies in Antiphospholipid Syndrome and Systemic Lupus Erythematosus

Abstract: Objective: To define the role of IgA antibodies to cardiolipin (aCL) and IgA antibodies to beta-2 glycoprotein 1 (anti-β2-GP1) in the development of vascular complications in patients with antiphospholipid syndrome (APS) and systemic lupus erythematosus (SLE). Material and methods: A total of 187 patients with one of the following diagnoses: primary APS (PAPS), probable APS, SLE with APS, and SLE without APS. The comparison group consisted of 49 patients with other rheumatic diseases (RD), the control group in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated a link between the IgA isotypes and thrombosis ( Pericleous et al, 2016 ; Tebo et al, 2016 ). Recently, Reshetnyak et al reported that IgA aCL and IgA aβ2GPI had a high specificity (95% and 93%) but a low sensitivity (54% and 44%) in detecting APS ( Reshetnyak et al, 2022 ). The diagnostic value of IgA aPL is worthy of further study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a link between the IgA isotypes and thrombosis ( Pericleous et al, 2016 ; Tebo et al, 2016 ). Recently, Reshetnyak et al reported that IgA aCL and IgA aβ2GPI had a high specificity (95% and 93%) but a low sensitivity (54% and 44%) in detecting APS ( Reshetnyak et al, 2022 ). The diagnostic value of IgA aPL is worthy of further study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with primary APS and patients with secondary APS associated to SLE, have a higher prevalence and a higher level of IgA aCL and IgA anti-β 2GPI, when compared to patients with SLE or other autoimmune diseases and without APS. Moreover, these antibodies demonstrate an important correlation with thrombotic events [ 11 ]. aPLs positivity can worsen the prognosis of several diseases, which was well demonstrated by Ruaro and coll., who described a correlation between antiphospholipid antibody positivity and pulmonary embolism events in sarcoidosis patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The value of IgA aβ2GPI in APS diagnosis is still controversial. Some studies support their clinical relevance in APS 4–6 while others failed to demonstrate an added value of this isotype 7,8 . Otherwise, aβ2GPI‐IgA have been linked to atherosclerotic disease, 9 chronic renal disease, 10 early mortality after heart transplantation 11 and cardiovascular mortality in hemodialysis patients 12 .…”
Section: Introductionmentioning
confidence: 99%